2015
DOI: 10.1007/s00299-015-1910-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of VaPAT1, a GRAS transcription factor from Vitis amurensis, confers abiotic stress tolerance in Arabidopsis

Abstract: VaPAT1 functions as a stress-inducible GRAS gene and enhanced cold, drought and salt tolerance in transgenic Arabidopsis via modulation of the expression of a series of stress-related genes. The plant-specific GRAS transcription factor family regulates diverse processes involved in plant growth, development and stress responses. In this study, VaPAT1, a GRAS gene from Vitis amurensis was isolated and functionally characterized. Sequence alignment and phylogenetic analysis showed that VaPAT1 has a high sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 52 publications
2
53
0
1
Order By: Relevance
“…For example, Yang et al (2012) confirmed that the activities of POD, SOD and CAT increased in plants over-expressing OsMYB2 , under salt stress. However, Yuan et al (2015) reported that under cold stress, antioxidase activity was not significantly different in VaPAT1- over-expressing plants compared to WT plants. Shingote et al (2015) found POD and CAT activities fell, while SOD activity increased in transgenic plants under cold stress.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Yang et al (2012) confirmed that the activities of POD, SOD and CAT increased in plants over-expressing OsMYB2 , under salt stress. However, Yuan et al (2015) reported that under cold stress, antioxidase activity was not significantly different in VaPAT1- over-expressing plants compared to WT plants. Shingote et al (2015) found POD and CAT activities fell, while SOD activity increased in transgenic plants under cold stress.…”
Section: Discussionmentioning
confidence: 95%
“…The genes in the PAT1 branch of the GRAS family regulate diverse functions in plants. Several A. thaliana genes belong to the AtPAT1 subbranch of the GRAS family, namely AtSCL21, AtSCL5, AtSCL13, and AtSCL1 (Yuan et al, 2016). Two rice genes, OsCIGR1 and OsCIGR2, are grouped in the same sub-branch.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of cold‐responsive genes may provide resources to improve cold tolerance in grapevine through molecular breeding. Our laboratory has identified various TF genes, such as VaCBF4 (Li et al ., ), VvICE1 (Li et al ., ), VaERF057 (Sun et al ., ), VaPAT1 (Yuan et al ., ), and VaAQUILO (Sun et al ., ), which are inducible by cold stress and that confer cold tolerance when expressed in A. thaliana or grapevine.…”
Section: Introductionmentioning
confidence: 99%